Epigenetic changes and alternate promoter usage by human colon cancers for expressing DCLK1-isoforms: Clinical Implications - O’Connell, Malaney R. (Sci Rep, 2015)
DCLK1 specifically marks colon/pancreatic cancers in mice, and is expressed by human colon adenocarcinomas (hCRCs). Down-regulation of DCLK1 results in loss of cancer-stem-cells (CSCs), and inhibits spheroidal/xenograft growths from hCRC-cells. The 5′-promoter of DCLK1-gene is reportedly hypermethylated in hCRCs, resulting in loss of expression of DCLK1-transcripts, originating from 5′(α)-promoter (termed DCLK1-L, in here). However, in mouse colon-tumors, 5′-promoter of DCLK1-gene remains unchanged, and DCLK1-L, originating from 5′(α)-promoter, is expressed. We hypothesized that elevated levels of DCLK1-protein in hCRC-cells, may be transcribed/translated from an alternate-promoter. Several in silico and molecular biology approaches were used to test our hypothesis. We report for the first time that majority of hCRCs express short-transcripts of DCLK1 (termed DCLK1-S, in here) from an alternate β-promoter in IntronV of the gene, while normal-colons mainly express DCLK1-L from 5′(α)-promoter. We additionally report an important role of β-catenin and TCF4/LEF binding-sites for activating (α)-promoter, while activated NF-κBp65 (bound to NF-κB-cis-element), activates (β)-promoter in cancer-cells. DCLK1-S expression was examined in a cohort of 92 CRC patients; high-expressors had significantly worse overall-survival compared to low-expressors. Our novel findings’ regarding usage of alternate (β)-promoter by hCRCs, suggests that DCLK1-S may represent an important target for preventing/inhibiting colon-cancers, and for eliminating colon-CSCs.